Electro dialysis reversal (EDR) performance for reject brine treatment of reverse osmosis desalination system. - Hossein Ataei Far; Amir Hessam Hassani; Lobat Taghavi; Mojtaba Fazeli; Abdollah Rashidi Mehrabadi (PLoS ONE, 2022)
In this study, the performance of bench-scale EDR was evaluated using the samples taken from the 1st and the 2nd stage RO from the Brackish Water Reverse Osmosis (BWRO) plant in Eshtehard, Iran. The measurements indicated that original TDS of the aquifer brackish water was equal to 3,229-3,664 mg/L, whereas TDS of the 1st stage RO brine was between 5,500 and 7,700 mg/L, that TDS of the 2nd stage RO brine was in the range of 9,500-10,600 mg/L. A batch bench-scale EDR system of 12 l/h was used with a direct electric current at three different scenarios. In the first, the brine was fed at 20°C (as a reference regulated point). In the second, temperature (14, 20, 26.5°C), and in the third, voltage were changed (6, 12, 18, 24 V) to investigate their influences on performance of the EDR process, while the other operational parameters (feed flow rate, recovery ratio, quality of feed brine)were kept constant. Based on the data analysis using the ANOVA and DUNCAN tests for the second and third scenarios, it was observed that the optimum TDS removal efficiency of the EDR process can be at temperature of 26.5°C and voltage of 18 V. On the other hand, the successful performance of the bench-scale EDR in reducing the 29,000 mg/L TDS and the 45,000 μmhos/cm EC of the 2nd stage brine to 1,716 mg/L (TDS) and 2,640 μmhos/cm (EC) (at 26.5°C and 24V) could be considered as the main achievement of this research. Overall, the hybrid process RO-EDR-RO can be considered as the best technical, environmental and economical scenario for the development of Eshtehard Desalination Plant phase 2 at full scale.